Novel materials and crystallizer design for freeze concentration - Alison Emslie Lewis; Jemitias Chivavava; Lerato Audrey Motsepe; Buhle Nxiwa; Karabo Netshiomvani; Njabulo Zimu (Scientific African, 2023)
When wastewater streams or seawater are desalinated, the waste product is a hypersaline brine stream which is usually disposed of or stored in evaporation ponds. Eutectic Freeze Crystallization (EFC) is a novel treatment technology for these hypersaline brines that can recover both water and dissolved salts. It works by cooling the stream to the Eutectic temperature, at which point both ice and salt will crystallize. The ice, being less dense than the solution, floats, and the salt, being denser, will sink – thus effecting a gravity separation.Theoretically, EFC can result in zero liquid discharge (ZLD) and has several advantages over conventional separation techniques, including low energy consumption; high quality products and it requires no additional chemicals. It can also be combined with other separation technologies to optimise the separation process.Although it sounds simple, an EFC process can be difficult to design and operate effectively, since each of the elements has its own complexity. Specifically, the issue of ice scaling is one of the major challenges in implementing EFC.Therefore, in this study, we focussed on ice scaling in a freeze concentration system i.e ice crystallization only; without the salt crystallization component that would define the process as an EFC process.We investigated two approaches to scaling reduction:The first was modification of the heat exchanger surface, where we investigated the effect of three different heat exchanger surfaces on ice scaling: a novel polypropylene graphite (PP GR) material, Stainless Steel 316 (SS316) and Aluminium. These three materials were tested in a small-scale Column Crystallizer (CC).The second method was by designing a Continuously Stirred Column Crystallizer (CSCC), which aimed to improve the hydrodynamics independent of pumping, to improve on the heat and mass transfer distribution across the crystallizer and to improve product purity by providing a larger product separation zone. The focus was on producing an efficient crystallizer design, bearing current industrial implementation hurdles in mind.This study confirmed that using materials of low surface energy has the potential to increase the scaling induction times and reduce the severity of ice scaling, hence improving process efficiency. The outcome of the initial, small-scale study provided the required evidence to support scaling up the column crystallizer using PP GR as an HX material of choice.The study also showed that the unique multicompartment mixing system of the novel CSCC led to high supercoolings and long induction times being attained. The column design provides a larger disengagement zone than a conventional column, which has the potential to improve the separation efficiency, and hence the product purity.In summary, with the correct choice of heat exchanger material and appropriate crystallizer design, we have shown that one of the major challenges i.e. ice scaling, can be overcome. This paves the way for EFC being able to be used for the treatment of hypersaline brines, not only at laboratory scale, but also at larger, commercial scales.